2017
DOI: 10.3928/1081597x-20170201-02
|View full text |Cite
|
Sign up to set email alerts
|

Customized Topography-Guided Corneal Collagen Cross-linking for Keratoconus

Abstract: At 1 year postoperatively, TG-CXL seems to be as safe as C-CXL with stronger flattening in Kmax and I index and better improvement in CDVA. TG-CXL induces a biological gradient between the cone and the surrounding area that facilitates nerve and cell recovery. [J Refract Surg. 2017;33(5):290-297.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…The customized UVA treatment pattern consisted of a graded pattern of three concentric ellipses of decreasing energy dose from center to periphery. Maximum energy dose applied was 15 J/cm 2 , consistent with previous studies of customized cross-linking using 30 mW/cm 2 irradiance in patients with keratoconus [ 6 , 7 , 9 , 11 ]. The treatment pattern was centered on the location of the posterior float identified on corneal tomography, with the diameter of the treatment ellipses customized to cover the cone area, according the method previously described by Seiler et al [ 10 ].…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…The customized UVA treatment pattern consisted of a graded pattern of three concentric ellipses of decreasing energy dose from center to periphery. Maximum energy dose applied was 15 J/cm 2 , consistent with previous studies of customized cross-linking using 30 mW/cm 2 irradiance in patients with keratoconus [ 6 , 7 , 9 , 11 ]. The treatment pattern was centered on the location of the posterior float identified on corneal tomography, with the diameter of the treatment ellipses customized to cover the cone area, according the method previously described by Seiler et al [ 10 ].…”
Section: Methodssupporting
confidence: 84%
“…The treatment is applied using a programmable UVA delivery device with integrated eye tracking to selectively activate the riboflavin photosensitizer in the targeted areas of the cornea [ 8 ]. Several controlled clinical studies have demonstrated greater corneal regularization in eyes treated with epi-off customized cross-linking as compared to conventional broad beam CXL, with greater flattening in the areas of steepest corneal curvature, compensatory steepening in the untreated surrounding cornea, and resultant gains in visual function [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Mosaic delivery system (KXL II, Avedro Inc.,Waltham, MA, USA) offers customised cross-linking (photorefractive intrastromal cross-linking- PiXL). Initial studies on customised cross-liking report greater corneal regularisation and reduction in maximum keratometry than conventional cross-linking [ 95 - 97 ].…”
Section: Customised Cross-linkingmentioning
confidence: 99%
“…Various other studies have been published since demonstrating the results of the customized approach. [ 71 72 73 74 ] The use of varying treatment patterns including customized toric, asymmetric arcuates, and concentric circles has been described. An important aspect is to determine the localization of the irradiation patterns.…”
Section: Customized Corneal Collagen Cross-linking For Keratoconus: Imentioning
confidence: 99%